2011
DOI: 10.1177/0969733011410093
|View full text |Cite
|
Sign up to set email alerts
|

Changes in how ICU nurses perceive the DNR decision and their nursing activity after implementing it

Abstract: This study investigated the perceptions and attitudes of ICU nurses towards the 'do not resuscitate' (DNR) decision and changes in their nursing activities after implementation of the DNR decision in South Korea. A data survey was conducted in South Korea between August and October 2008, with a convenience sample of 252 ICU nurses who had more than one year of clinical experience. The data were collected via a self-administered questionnaire. Most of the nurses perceived the necessity of the DNR decision in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 10 publications
7
42
0
1
Order By: Relevance
“…This has raised the concern that at least some DNR patients might be medically or psychologically abandoned [9]. Although these studies did not specifically demonstrate abandonment, they may have reflected misinterpretation by or confusion of healthcare professionals about the proper level of medical care that should be provided to DNR patients [5][6][7][8]. Some healthcare professionals may have believed that DNR patients were eligible to receive medical interventions to extend life short of an arrest, while others thought that DNR was, essentially, an order for comfort care only.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This has raised the concern that at least some DNR patients might be medically or psychologically abandoned [9]. Although these studies did not specifically demonstrate abandonment, they may have reflected misinterpretation by or confusion of healthcare professionals about the proper level of medical care that should be provided to DNR patients [5][6][7][8]. Some healthcare professionals may have believed that DNR patients were eligible to receive medical interventions to extend life short of an arrest, while others thought that DNR was, essentially, an order for comfort care only.…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, several studies have shown that healthcare professionals tended to provide less medical care after DNR orders were written for patients [5][6][7][8]. This has raised the concern that at least some DNR patients might be medically or psychologically abandoned [9].…”
Section: Introductionmentioning
confidence: 99%
“…그러나 임상 현장에서 일부 의료인들은 DNR 을 치료를 하지 않는 것(Do not treat)으로 잘못 이해하 는 경향이 있다 (7). 일부 의사들은 DNR을 치료의 포기 로 간주하여 대부분의 치료를 줄이거나 소홀히 하고 (7,8), 간호사들 또한 DNR 환자에 대한 간호 행위를 줄 이거나 우선순위를 낮게 생각하는 경향이 있는 것이 사 실이다 (9). 그 이유는 의료진마다 DNR에 대한 해석과 태도에 혼란이 있음에도 불구하고 이를 바로잡아 줄 교 육이나 구체적 실무 지침이 없으며, 환자나 가족과의 적극적인 의사소통과 이를 통한 구체적 치료방향에 대한 의사결정 과정이 부족하기 때문이라고 할 수 있다 (7).…”
Section: 연구의 필요성unclassified
“…reduced out-of-hours medical escalation, contacting the outreach team, frequency of nursing observations, reduced pain relief and altered fluid intake), despite clear guidelines that DNACPR orders applied only to CPR. Other examples of the misinterpretation of care for patients with DNACPR orders included where some doctors and nurses believed that nursing observations would be reduced 63,97 or remain unchanged, 100 that contact with outreach teams and other medical staff and out-of-hours medical escalation would be less frequent, although nurses less often felt that this occurred than doctors. 97 It was also suggested that pain relief and amounts of fluids would be altered 97 and one Finnish study 63 noted that basic care was reduced for patients with a DNACPR order.…”
Section: Treatment and Carementioning
confidence: 99%
“…Thirty-four articles are included here, 13,14,16,38,39,41,[63][64][65][67][68][69][70]73,75,76,[78][79][80][81][82][83][84]87,[89][90][91]93,95,97,98,[100][101][102] of which 18 are questionnaire or survey studies; six of these are high-quality studies, 69,70,78,93,95,102 one is of medium quality 38 and 11 are of low quality. [63][64][65]67,68,73,75,83,90,100,...…”
Section: Implementing the Decisionmentioning
confidence: 99%